Mitral regurgitation and in-hospital mortality in patients with heart failure and low flow low gradient aortic stenosis. (4th February 2022) - Ferruzzi, GJ; Peluso, AP; Attisano, T; Migliarino, S; Vigorito, F; Bellino, M; Iuliano, G; Silverio, A; Provenza, G; Cristiano, M; Galasso, G; Baldi, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Aim: this study sought to determine the prevalence, clinical impact, and in-hospital outcome of moderate to severe mitral regurgitation (MR) in patients with low-flow, low-gradient aortic stenosis (LFLG-AS) hospitalized for heart failure (HF). Methods: Patients with aortic valve thickness and aortic velocities >2.5 m/s hospitalized for heart failure in a single referral center were prospectively enrolled from 2013 to 2021. LFLG-AS was defined as indexed aortic valve area (iAVA) ≤0.6 cm2/m2, mean transaortic gradient <40 mmHg and stroke volume index <36 ml/m2. Complete demographic, clinical characteristics and echocardiographic data were collected. Mitral regurgitation severity was graded according to current guidelines. Patients were divided into two subgroups according to MR severity: no/mild MR vs moderate/severe MR. In hospital all cause death has been considered as the primary outcome. Results: A total of 136 patients  (78 ± 9 yy; 68 (50%) male) hospitalized for HF with a new diagnosis of LFLG-AS were included in the study. The most frequent comorbidities were hypertension (121, 89%), dyslipidemia (106, 78%), chronic kidney disease (85, 63%), diabetes (56, 41%) and obesity (44, 32%). Atrial fibrillation/flutter was detected in 61 (45%) patients. Moderate to severe MR was detected in 33%. Mean functional NYHA class was 2, 8 ± 0, 8. Concerning echocardiographic evaluation, the mean gradient of the aortic valve was 26 ± 7 mmHg and the mean iAVA was 0.42 ± 0.10 cm2/m2. The mean left ventricular ejection fraction (LV EF) was 46 ± 13%. Paradoxical LFLG-AS with a preserved LV EF was detected in 73 patients (54%) and the LFLG-AS with a low LV EF was detected in 63 (46%). In this population, 26 patients (19%) underwent surgical valvular replacement, 15 patients (11%) had aortic percutaneous valvuloplasty and 33 patients (24%) underwent TAVI. The remaining patients (45%, n = 62) were maintained under optimized medical therapy. In-hospital death occurred in 17 (12, 5%) patients (just 1 for non-cardiovascular causes). Moderate/severe MR was detected in 44 (33%) patients. When comparing the two subgroups statistically significant differences between age (p = 0, 035), male sex (p = 0, 028), atrial fibrillation/flutter (p = 0, 003), obesity (p = 0, 040) and in-hospital mortality (p = 0, 013) were detected. In the overall population the multivariate regression analysis showed that only the presence of moderate /severe MR was a significant independent predictor of all-cause in-hospital death (p = 0.017 ; OR 3.571 ; IC  1.257-10.151). Conclusion. Moderate to severe MR is frequently detected in patients with LFLG AS and HF. In this peculiar cohort significant MR has a negative impact on outcome and is independently associated with in-hospital mortality.